Analisis Karya Kolase Tema Amfibi Menggunakan Bahan Origami Karya Siswa Kelas XI IPS Sekolah SMAS Budi Satrya T.A 2024/2025 - Raja Kores Galatia Sitorus; Nelson Tarigan (Akuntansi, 2026)
This study aims to determine the results of collage work by applying collage on plywood media using origami reviewed from the "principles of fine art" at SMAS Budi Satrya school. The sample used was 16 students of class XI IPS in creating collages. The results of the study obtained an average value of 88.70 (good) reviewed from the principle of unity obtained an average value of 89.29 (good), reviewed from the principle of balance obtained an average value of 87.35 (good), reviewed from the principle of rhythm obtained an average value of 88.10 (good), reviewed from the principle of emphasis obtained an average value of 89.31 (good), reviewed from the principle of proportion obtained an average value of 89 (good), and reviewed from the principle of harmony obtained an average value of 89.14 (good). So it can be concluded that the results obtained, students are good at applying the principles of fine art in creating collages with plywood media.